Delayed conception in women with low-urinary iodine concentrations: a population-based prospective cohort study. Issue 3 (11th January 2018) - Mills, J L; Buck Louis, G M; Kannan, K; Weck, J; Wan, Y; Maisog, J; Giannakou, A; Wu, Q; Sundaram, R
Abstract: STUDY QUESTION: Is iodine deficiency associated with decreased fecundability? SUMMARY ANSWER: Moderate to severe iodine deficiency is associated with a 46% decrease in fecundability. WHAT IS KNOWN ALREADY: Iodine deficiency is common in women of childbearing age but its effect on fecundability has not been investigated. STUDY DESIGN, SIZE, DURATION: The LIFE Study, a population-based prospective cohort study, enrolled 501 women who had discontinued contraception within 2 months to become pregnant between 2005 and 2009. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women reported on risk factors for infertility by interview then kept daily journals of relevant information. Women used fertility monitors to time intercourse relative to ovulation then used home digital pregnancy tests to identify pregnancies on the day of expected menstruation. Urine samples for iodine analysis were collected on enrollment. MAIN RESULTS AND THE ROLE OF CHANCE: Samples were in the deficiency range in 44.3% of participants. The group whose iodine–creatinine ratios were below 50 μg/g (moderate to severe deficiency) had a 46% reduction in fecundity ( P = 0.028) compared with the group whose iodine–creatinine ratios were in the adequate range: adjusted fecundability odds ratio of becoming pregnant per cycle, 0.54 (95% confidence interval 0.31–0.94). LIMITATIONS, REASONS FOR CAUTION: Iodine concentrations vary within individuals over time, so the data must be interpreted by group as we have done; residual confounding is possible. WIDER IMPLICATIONS OF THE FINDINGS: Significant delays in becoming pregnant occur at iodine concentrations that are common in women in the USA and parts of Europe. Replicating these findings will be important to determine whether improving iodine status could be beneficial in improving fecundability. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the Intramural Research Program, Eunice Kennedy Shriver National Institute of Child Health and Human Development, National Institutes of Health, USA. Contracts N01-HD-3-3355; N01-HD-3-3356; N01-HD-3-3358 and HHSN275201100001l/HHSN27500007. None of the authors has any conflict of interest to declare.